A deep acting perspective generation Y hotel employees' workplace deviance. Issue 2 (31st January 2020) - Yu, Yanping; Kim, Haemi; Qu, Hailin
Abstract : Purpose: This study aims to develop a measurement scale to assess generation Y China hotel employees' workplace deviance and then investigate the effect of generation Y employees' deep acting on workplace deviance by focusing on the mediating effect of emotional exhaustion and the moderating effect of organizational identification. Design/methodology/approach: The study first adopts a mixed-methods approach to develop the scale of generation Y hotel employees' workplace deviance, then multiple data is collected targeting 580 hotel employees by a three-stage survey. Structural equation modeling (SEM) and a hierarchical regression analysis were used to test the hypotheses. Findings: Workplace deviance of generation Y hotel employees in China was divided into two dimensions, aggression and neglect. Deep acting was found to be negatively related to workplace deviance, and emotional exhaustion had a mediating effect on the relationship between deep acting and workplace deviance. Organizational identification strengthened the effect of deep acting on neglect and the effect of deep acting on emotional exhaustion, whereas it did not moderate the relationship between deep acting and aggression. Originality/value: First, this study provides a more powerful explanatory perspective on the conservation of resources theory to explore future research by especially targeting generation Y employees. Second, this study develops the elements of workplace deviance structure of generation Y hotel employees, especially in the Chinese cultural context. Third, it explores the inherent mechanism of how and why deep acting impacts workplace deviance.